Factoring Future Generations Into Universities' Strategic Intent: Could a Law Help? - Davidson, Jane (Frontiers in Sustainability, 2021)
Wales is the first country in the world to have put into law the protection of future generations; the first country to have a legal mechanism through the Act to deliver on the Sustainable Development Goals and the first country to have put the Brundtland definition of sustainable development into law. What does this mean for the values taught in Welsh universities and how can the university role be re-purposed in the interests of future generations? Building on her research for the book #futuregen: Lessons from a Small Country which was published this year, Jane Davidson, who, in her previous role as Minister in Welsh Government, proposed what is now the Well-being of Future Generations (Wales) Act 2015, will explore the opportunities from this new values framework to transform the university sector, in particular the student experience in Wales, and whether there are further lessons that would be valuable elsewhere.